The persistence of error: a study of retracted articles on the Internet and in personal libraries...[corrected] [published erratum appears in J MED LIBR ASSOC 2012; 100(4):329] - Davis, Phillip M. (Journal of the Medical Library Association, 2012)
Objective: To determine the accessibility of retracted articles residing on non-publisher websites and in personal libraries. Methods: Searches were performed to locate Internet copies of 1,779 retracted articles identified in MEDLINE, published between 1973 and 2010, excluding the publishers' website. Found copies were classified by article version and location. Mendeley (a bibliographic software) was searched for copies residing in personal libraries. Results: Non-publisher websites provided 321 publicly accessible copies for 289 retracted articles: 304 (95%) copies were the publisher' versions, and 13 (4%) were final manuscripts. PubMed Central had 138 (43%) copies; educational websites 94 (29%); commercial websites 24 (7%); advocacy websites 16 (5%); and institutional repositories 10 (3%). Just 15 (5%) full-article views included a retraction statement. Personal Mendeley libraries contained records for 1,340 (75%) retracted articles, shared by 3.4 users, on average. Conclusions: The benefits of decentralized access to scientific articles may come with the cost of promoting incorrect, invalid, or untrustworthy science. Automated methods to deliver status updates to readers may reduce the persistence of error in the scientific literature.